Molecular Mechanisms of Lymph Node Metastasis in Gallbladder Cancer: Insights into the Tumor Microenvironment - Qingyu Tang; Yichen Guan; Yubo Ma; Qi Li; Zhimin Geng (Biomedicines)
Gallbladder cancer (GBC) is a highly aggressive malignancy with a propensity for lymph node metastasis (LNM), which significantly worsens prognosis. This review explores the molecular mechanisms underlying LNM in GBC, focusing on the roles of vascular endothelial growth factors (VEGFs), chemokines, cancer-associated fibroblasts (CAFs), tumor-associated macrophages (TAMs), hypoxia-inducible factors (HIFs), and non-coding RNAs (ncRNAs) in shaping the tumor microenvironment (TME). Unique features of GBC, such as its bile-rich microenvironment and hypoxia-driven lymphangiogenesis, are highlighted. We discuss how these factors promote lymphangiogenesis, immune evasion, and extracellular matrix (ECM) remodeling, collectively facilitating LNM. Potential therapeutic targets, including VEGF-C/D pathways, matrix metalloproteinase (MMP) inhibitors, and immune-modulating therapies, are also reviewed. Future research integrating single-cell omics and patient-derived organoid models is essential for advancing precision medicine in GBC.